2006
DOI: 10.1007/s11237-006-0042-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the local environment and state of the immobilized ligand on its reaction with a macromolecular receptor

Abstract: We consider a simple statistical model for interaction between a macromolecular receptor and a surface functionalized with low molecular weight ligands of the same type. For the example of the reaction between immobilized sulfamethoxazole and a selective antibody, we have used surface plasmon resonance to demonstrate that the proposed approach is appropriate for describing the dependence of the adsorption capacity on the surface density of the immobilized ligand and its charge state.Processes occurring at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The result obtained, on one hand, supports the description of the interface processes proposed above and, on the other, confirms a significant level of nonspecific adsorption (~250¢¢-300¢¢) characteristic of the surface architecture studied. The latter effect is probably due to the hydrophobic nature of the base matrix, whose high nonspecific adsorption of proteins has been noted previously [3,12].…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…The result obtained, on one hand, supports the description of the interface processes proposed above and, on the other, confirms a significant level of nonspecific adsorption (~250¢¢-300¢¢) characteristic of the surface architecture studied. The latter effect is probably due to the hydrophobic nature of the base matrix, whose high nonspecific adsorption of proteins has been noted previously [3,12].…”
mentioning
confidence: 65%
“…The immobilization of SMX was carried out similarly to our previous method [3] by binding the surface hydroxyl groups and terminal SMX amino groups by the trichlorotriazine heterocycle. In the same work, we carried out a detailed examination of the interaction for medium and low densities of the surface sites and showed that the system under such conditions operates satisfactorily.…”
mentioning
confidence: 99%
See 3 more Smart Citations